The surface diffusion of gold atoms on gold electrodes in acid solution and its dependence on the presence of foreign adsorbates - Alonso, C. (1990)
The surface diffusion coefficient (Ds) of Au atoms in 0.5 M H2SO4 at 298 K has been determined from the time dependence of the surface roughness factor of electrodispersed Au electrodes in 0.5 M H2SO4. The value of Ds for 0.5 M H2SO4 is 5 × 10−14 cm2 s−1, a figure which depends considerably on the presence of adsorbable species in solution. Thus, the adsorption of pyridine produces a remarkable decrease of Ds, whereas the adsorption of Cl− ion results in the opposite effect. The corresponding values of Ds are 1.2 × 10−14 cm2 s−1 for 0.5 M H2SO4 + 0.1 M pyridine, and 2.5 × 10−13 cm2 s−1 for 0.5 M H2SO4 + 5 × 10−4 M KCl. These results are interpreted through the influence of the adsorbate on the Au surface atom diffusion mechanism.